2020
DOI: 10.1097/md.0000000000021798
|View full text |Cite
|
Sign up to set email alerts
|

Mining prognostic factors of extensive-stage small-cell lung cancer patients using nomogram model

Abstract: This study is to establish the nomogram model and provide clinical therapy decision-making for extensive-stage small-cell lung cancer (ES-SCLC) patients with different metastatic sites using the Surveillance, Epidemiology, and End Results (SEER) Program. A total of 10,025 patients of ES-SCLC with metastasis from January 2010 to December 2016 were enrolled from the SEER database. All samples were randomly divided into a derivation cohort and a validation cohort, and the derivation cohort was divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…These were some unique disease features for elderly SCLC patients. In addition, we identified ten independent prognostic factors for OS and CSS, which were consistent with the previous findings [ 7 , 13 16 , 23 25 ]. Our model indicated that chemotherapy made the greatest contribution to the prognostic score.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These were some unique disease features for elderly SCLC patients. In addition, we identified ten independent prognostic factors for OS and CSS, which were consistent with the previous findings [ 7 , 13 16 , 23 25 ]. Our model indicated that chemotherapy made the greatest contribution to the prognostic score.…”
Section: Discussionsupporting
confidence: 91%
“…Our model indicated that chemotherapy made the greatest contribution to the prognostic score. Multiple studies have proved that chemotherapy, as the most important treatment for SCLC, can prolong the survival time of patients [ 7 , 13 , 15 , 23 , 26 ]. Our analysis also indicated that AJCC stage and surgery had greater impacts on patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Two retrospective studies of DM-SCLC based on the SEER database have been published. The study from Hongxiang Gao [ 14 ] reported 10025 patients with DM-SCLC from January 2010 to December 2016 who were included in the SEER database. The variables included in the predictive model in that study were age, sex, race, T stage, N stage, distant metastatic site, and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…At present, standard treatment for patients with ES-SCLC consists of 4-6 cycles of platinumbased chemotherapy with immunotherapy. However, approximately 20% of those diagnosed with SCLC are not offered chemotherapy (14). The chance of being offered treatment decreased with PS.…”
Section: Discussionmentioning
confidence: 99%